The enrichment of Kelulut (Trigona spp.) feeding plants for its sustainability in mangrove ecotourism Beras Basah Village, Langkat Regency, North Sumatra, Indonesia - Dewi, Rita Rosmala (Journal of Saintech Transfer, 2025)
The cultivation of Trigona honey bees by the "Kelompok Tani Peduli Pesisir" (Coastal Care Farmer Group) has strong potential for rapid development due to the abundant availability of food plants that support the life of kelulut bees (Trigona spp.), particularly from home gardens in mangrove areas. The diversity of plant species is crucial for ensuring a steady supply of nectar, pollen, and resin, which directly impacts honey production. However, limited community knowledge about suitable plant species and the lack of plant variety pose challenges to sustainable Trigona spp. beekeeping. This community service initiative aims to introduce potential food sources for kelulut bees and provide plants to enrich the variety of feed sources, ensuring availability year-round. Activities include 1) preparing plant materials and planting media, 2) planting fruit trees, and 3) conducting educational outreach. As a result, farmers’ knowledge and the diversity of beneficial perennial plants such as mango (Mangifera indica), jackfruit (Artocarpus heterophyllus), and water apple (Syzygium aqueum) have increased, contributing to the sustainable development of Trigona spp. bee cultivation.